Fiscal adjustments, labour market flexibility and unemployment - Agnello, Luca (2014)
Using a panel of 17 countries for 1978-2009, we find that tax-driven consolidations increase unemployment by 0.25 percentage points. Labour market flexibility mitigates this: a one-point rise in the flexibility index reduces youth (long-term) unemployment by 0.6-0.7 (1.8-2.2) percentage points.